Perancangan Sistem Informasi Open Data Pada Industri Kecil dan Menengah Kota Padang Berbasis Web - Junaldi - -; Hidra Amnur -; Defni - - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2016)
Padang society known as people who have the spirit of entrepreneurship, it is marked by the increasing number of small and medium industries in the city of Padang. Limitations of this information gives the impression of small and medium industries that runs itself. This article will produce a product web-based information system that is open data is the latest in the field of information technology. This information system will as a place for people to obtain information data in the form of products, the location of the small and medium industrial enterprises in the city of Padang. This information system also can be used as a medium for the industry small and medium enterprises in the city of Padang to obtain information